Digital marketing trends in food and beverage industry - Movla-zada, Ulviyya (2020)
The Master thesis focuses on the digital marketing trends and instruments used in Food and Beverage industry in Azerbaijani Republic. The aim is to find out which digital marketing instruments are mostly used in food and beverage industry nowadays, which of them are really effective for both, consumer and producer’s sides and which of them most probably will be used in the future in Azerbaijani Republic. Both – consumer’s side and producer’s side have been analyzed, the quantitative data has been collected through the survey, processed and empirical research has been done. The research showed that the marketers and businessowners in the target country have a great potential to achieve success in Food and Beverage industry with the help of correctly used Digital Marketing tactics. Several possible improvements were identified, and the recommendations were provided by the author.